Jamu Preservation And Purchase Intention: Innovation Strategies In Acaraki Jamu - Haninda Puspa, Margaret Levana; Berutu, Feronika (Journey : Journal of Tourismpreneurship, Culinary, Hospitality, Convention and Event Management, 2025)
This study explores innovation as a strategy to preserve traditional jamu and increase consumer interest in the modern era, focusing on Acaraki Jamu as a case study. Using a qualitative descriptive method, data were collected through observation, in-depth interviews with five informants (a marketing manager, a barista, and three young consumers), and documentation. The findings show that Acaraki Jamu implements innovation through product presentation, modern café concepts, and the use of coffee-style preparation methods. These strategies have successfully transformed the image of jamu from a traditional herbal drink to a contemporary lifestyle choice, especially among younger consumers. Acaraki also utilizes digital marketing and minimalist interior design to support consumer engagement. The study concludes that innovation plays a vital role in reviving traditional cultural products by making them more accessible and appealing to modern audiences. This research contributes to the understanding of how cultural heritage can adapt to current market demands through creative transformation, offering insights for businesses aiming to preserve tradition while attracting new market segments.